Cooperatives As Pillars Of A People-Centered Economy: A Constitutional Law Analysis Of Cooperative Regulation In Indonesia - A. Saiful Aziz; Mahmutarom Harun Rasyid; Jawade Hafidz; Tri Handayani; Ganis Vitayanty Noor (Faculty of Law, Universitas Pekalongan, 2025)
Cooperatives in Indonesia hold a unique constitutional status, enshrined in Article 33 of the 1945 Constitution, as instruments to achieve economic democracy and collective welfare. However, the practical realization of these ideals remains hindered by outdated regulatory frameworks, particularly Law No. 25 of 1992, which fails to reflect the dynamics of digital transformation,inclusive development, and modern governance. This study adopts a normative juridical method to examine the alignment of cooperative law with constitutional principles, focusing on the philosophical foundations, doctrinal interpretations, and historical evolution of cooperative governance. Through analysis of primary legal sources, academic literature, and recent policyinitiatives such as the Koperasi Merah Putih movementthis research reveals significant normative gaps, legal fragmentation, and institutional constraints within the current regulatory regime. The study argues for a fundamental legal reconstruction that positions cooperatives not as peripheral economic actors but as constitutional agents of equitable and sustainable development. It proposes key legal reforms including the recognition of digital cooperatives, enhanced accountability mechanisms, and integration with national development platforms. The findings emphasize the urgent need for a responsive, inclusive, and constitutionally grounded legal framework to revitalize the cooperative sector in post-pandemic and digitalIndonesia.